(untitled) (Research, Society and Development, 2022)
This study aimed to observe the effects of in intervention in children diagnosed with autism spectrum disorder (ASD) through the Motor Development Scale. This is a cross-sectional, exploratory study with a quantitative approach. Twenty-eight children with a clinical diagnosis of ASD of both sexes and their parents or guardians participated in the study. For data collection, the Motor Development Scale was used. The sample was divides into the following groups: Intervention Group (G1) and Control Group (G2) separated into Pre-intervention, Pre-control, post-intervention, and Pos-control analyses. Data were analyzed using the JASP statistical program (Version 0.11.1.). Comparisons between the means of the groups were made using analysis od variance with repeated measures and post-hoc analyzes using the Bonferronni test. Data homogeneity was verified using the Levene test. The effect size for the two-by-two comparisons of the Bonferroni test was estimated using Cohen’s “d” statistic. It was also verified that both in the General Motor Age domain and in the General Motor Quotient there was significance in the group where the Pre-intervention with the Post-intervention was compared, denoting a positive influence of the interventionist procedures used (p≤0,05). It is concluded that the intervention method used was beneficial for the children.